Burning down UNESCO a guide to innovative fundraising. - HOWARD BURTON (OPEN AGENDA PUBLISHING IN, 2021)
By a curious set of circumstances, Howard Burton found himself hired as a fundraising consultant at UNESCO's Paris headquarters. Overwhelmed by the bureaucratic double-speak and smug complacency that he encountered everywhere he went, he decided to use his clear-eyed analytical skills to ask a very different sort of question: What, exactly, was UNESCO doing that was actually worth funding in the first place?